Investment on Green Building as Strategy to Improve Company Value , Case Study of PT. Pembangunan Perumahan - Prabowo, Andek; Siahaan, Uke (The Indonesian Journal of Business Administration, 2015)
Abstract.PT. Pembangunan Perumahan is one of the many state-owned enterprises engaged in green building construction, where PT. Pembangunan Perumahan hoped to become a contractor who dominates this market. However, green building suffered some significant constraints especially with the idea that green building requires greater costs. This final projectcompares comparison between green building with conventional building especially in the calculation of the financial benefit for both the company and the clients, andthen formulate the company's strategy to increase the company's profitability and value PT. Pembangunan Perumahan.This study starts by assessing the business issue using external and internal analyses to find the root of problems. From there, it is found that the Red Ocean of construction industry makes PT. Pembangunan Perumahan has to make differentiation from others by becoming the company that leads the green building construction industry. However, the green building construction has higher initial investment and is not common in Indonesia. Therefore, PT. Pembangunan Perumahan is facing the condition that requires it to have competitive offering to clients from the green building construction. The competitive offering should have financial benefit, and also PT. Pembangunan Perumahan should know the benefit of green building for the company itself.This study then compares the green building and conventional buildings. From forecasting the projects, it is found that financially, focusing on green building gives higher value stock of the company, which is Rp 2,000 per share, compare to conventional one at Rp 1,500 per share. Moreover, it is also found that green building is more cost-efficiency for the customers in long term. Aside from the financial advantages, many other factors are more supportive of green building, including factors, technological and social environment. With the advantages provided by a green building, it is advisable that PT. Pembangunan Perumahan to be more focus on green building construction as stated in the strategy of achievement. This achievement strategy would bring PT. Pembangunan Perumahan to become a market leader within the next 10 years, furthermore PT. Pembangunan Perumahan should push government to make regulation to support green building. Keywords: Green Building, Construction, Investment Strategy, Finance Benefit, Valuation, Comparative Matrix, Strategy Map.Â Â